Pengaruh Konseling Kelompok Teknik Modelling Terhadap Kedisiplinan Siswa - Adiningrum, Wastiti; Saraswati, Sinta; Kurniawan, Kusnarto (Indonesian Journal of Guidance and Counseling: Theory and Application, 2017)
This study was conducted in SMK Plus Tunas Bangsa Kebasen Banyumas in 2017/2018 academic years. The purposes of this study is to knowing the influence of group counseling with modelling technique to discipline of the eleventh graders students in SMK Plus Tunas Bangsa Kebasen Banyumas. The type of this study is experimental study with pre experimental design. The subject of this study is 8 students from the eleventh graders vocational high school. The data was collected by student discipline questionnaire and use the test wilcoxcon analyisis. The result of this study showing that student discipline was changed  from low category to high category, can be conclude there are influence of group counseling with modelling technique to discipline of the eleventh  graders students in SMK Plus Tunas Bangsa Kebasen Banyumas.